Życie codzienne Marii Krystyny Habsburg (1923–2012) - Terteka, Małgorzata (Biuletyn Historii Wychowania, 2015)
The article presents the figure of Marie Christine Habsburg from Żywiec Town, Poland (1923-2012), especially her education at the Żywiec Court, where the court etiquette in the education of royal children from Lorraine Habsburg Dynasty was significant. It shows educational process of Marie Christine since her childhood till her studies at Faculty of Medicine at the Jagiellonian University in Cracow. It particularly describes the teaching process in her education. It lists the Subjects that she studied as well as her professors. It strongly emphasizes essential role of Language Training. At the background there was shown the dramatic fate of Habsburg Family of Żywiec during the Second World War, especially Karl Albrecht and his wife Alice neẻ Ancarcrona, who secretly supported Polish anti-Nazi underground and then they were persecuted and suffered in The Third Reich. It explains how educational process influenced patriotic attitude of Marie Christine.